Total cucurbitacins from Herpetospermum pedunculosum pericarp do better than Hu-lu-su-pian (HLSP) in its safety and hepatoprotective efficacy - Liu, Wen-Ya; Xu, Di; Hu, Zi-Yun; Meng, Hui-Hui; Zheng, Qi; Wu, Feng-Ye; Feng, Xin; Wang, Jun-Song (Frontiers in Pharmacology, 2024)
The pericarp of Herpetospermum pedunculosum (HPP) has traditionally been used for treating jaundice and hepatitis. However, the specific hepatoprotective components and their safety/efficacy profiles remain unclear. This study aimed to characterize the total cucurbitacins (TCs) extracted from HPP and evaluate their hepatoprotective potential. As a reference, Hu-lu-su-pian (HLSP), a known hepatoprotective drug containing cucurbitacins, was used for comparison of chemical composition, effects, and safety. Molecular networking based on UHPLC-MS/MS identified cucurbitacin B, isocucurbitacin B, and cucurbitacin E as the major components in TCs, comprising 70.3%, 26.1%, and 3.6% as determined by RP-HPLC, respectively. TCs treatment significantly reversed CCl4-induced metabolic changes associated with liver damage in a dose-dependent manner, impacting pathways including energy metabolism, oxidative stress and phenylalanine metabolism, and showed superior efficacy to HLSP. Safety evaluation also showed that TCs were safe, with higher LD50 and no observable adverse effect level (NOAEL) values than HLSP. The median lethal dose (LD50) and NOAEL values of TCs were 36.21 and 15 mg/kg body weight (BW), respectively, while the LD50 of HLSP was 14 mg/kg BW. In summary, TCs extracted from HPP demonstrated promising potential as a natural hepatoprotective agent, warranting further investigation into synergistic effects of individual cucurbitacin components.